Combined aesthetic interventions for prevention of facial ageing, and restoration and beautification of face and body - Fabi S; Pavicic T; Braz A; Green JB; Seo K; van Loghem JAJ (Dove Medical Press, 2017)
Sabrina Fabi,1 Tatjana Pavicic,2 André Braz,3 Jeremy B Green,4,5 Kyle Seo,6 Jani AJ van Loghem7 1Cosmetic Laser Dermatology, San Diego, CA, USA; 2Private Practice for Dermatology and Aesthetics, Munich, Germany; 3Division of the Policlínica Geral do Rio de Janeiro (PGRJ), Rio de Janeiro, Brazil; 4Skin Associates of South Florida, Miami, 5University of Miami Department of Dermatology, Miami, FL, USA; 6Seoul National University, Seoul, South Korea; 7Doctors Inc., Amsterdam, The Netherlands Abstract: The Merz Institute of Advanced Aesthetics Expert Summit was held in Prague, Czech Republic, from 19–20 November 2016. The meeting had a distinct advisory board character and invited aesthetic practitioners from all over the world to hear an international faculty present a range of keynote lectures and conduct live injection sessions with an emphasis on recent developments in combination aesthetic interventions for face and body rejuvenation and beautification. Aging is associated with changes in bones, muscles, ligaments, adipose tissue, and skin and, moreover, involves interactions among these tissue types. To achieve the most natural and harmonious rejuvenation of the face, all changes that result from the aging process should be corrected, which generally involves treatment with more than a single agent or technology. Presentations described innovative treatment algorithms for the face and body and focused on patients’ desires for natural-looking rejuvenation and how this requires a three-dimensional approach combining products that relax the musculature, volumize, and re-drape the skin. Besides treating the aging face, these procedures are increasingly used to enhance facial features as well as to delay facial aging in younger patients. The presentations covered patients from different ethnicities as well as the treatment of non-facial areas, with a particular focus on the use of Ultherapy® for skin lifting and tightening, and new aesthetic procedures such as Cellfina® and diluted Radiesse®. The current report provides a summary of key presentations from the meeting. Keywords: calcium hydroxylapatite, Cellfina, hyaluronic acid, incobotulinumtoxinA, Ultherapy